A Generic Framework for Sharing Data Using Attribute Based Cryptography in Hybrid Cloud - E. Poornima; Srinivasulu Sirisala; P. Dileep Kumar Reddy; G. Ramesh (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Now a days, large organizations are re-appropriating their information to the public cloud. But we should be cautious and improve the security about the data which is being shared. Maintaining the confidentiality among this public data is a major concern. To accomplish this a hybrid cloud Computing was intended to help safe & proficient contribution of information. Private cloud capacities go about as extension among clients & public cloud. As the organizations expand and create the hybrid Cloud requirement that can securely monitor information in clouds by entering interest. By providing online record sharing on the internet, the hybrid cloud has successfully met the needs of business customers. It offers an adaptable and versatile administrative environment. This property has made the hybrid cloud as mainstream administration in all businesses. This Work presents another plan of secure information sharing structure utilizing Proper cryptography for active assembly in hybrid cloud environment, which has the following features: Improved development of Ciphertext-Policy Attribute-Based Encryption through assigning ability of mutually encryption/decoding computation from client. Efficient access control through protection safeguarding highlights in cloud, In the client side decrease of calculations.